Pengaruh Bentuk Sediaan terhadap Potensi Antioksidan Ekstrak Etanol Daun Sirsak (Annona muricata L.) dalam Sistem Nanopartikel - Malinda Prihantini; Nopbrillian Fine Setya; Anisa Rizki Amelia; Tsabita Udkhiya Zulfa (Jurnal Ilmiah Medicamento, 2022)
Flavonoids in soursop leaf ethanol extract have various pharmacological effects but are easily degraded due to the influence of pH, oxygen, and intense light exposure. Encapsulation using chitosan polymer in nanoparticles is able to overcome these limitations. The formulation of the nanoparticle system in lotion and cream preparations can increase the comfort of use by consumers. Therefore, this study was conducted to determine the effect of lotion and cream dosage forms on the antioxidant activity of soursop leaf ethanol extract nanoparticles. Soursop leaf extraction was done by soaking at room temperature for 3 days using 70% ethanol as solvent. The soursop leaf ethanol extract nanoparticle system was prepared with three graded Soursop leaf ethanol extract concentrations F1 100 mg, F2 200 mg, and F3 300 mg. The nanoparticle system is then formulated into lotion and cream preparations. Evaluation of antioxidant activity was carried out by reacting it with DPPH, and the IC50 value of lotion preparation was obtained and showed the result was (F1) 83,34±0,130; (F2) 74,69±0,131; and (F3) 64,26±0,129 ppm, while the IC50 value of cream was (F1) 84,32±0,133; (F2) 75,35±0,130; and (F3) 63,74±0,120  ppm. The antioxidant activity of soursop leaf ethanol extract nanoparticles in lotion and cream preparations is included in the category of strong antioxidants. Statistical analysis using an independent t-test of the antioxidant activity showed p>0.05, so it was concluded that the ability to scavenge free radicals from soursop leaf ethanol extract in the nanoparticle system was not affected by the dosage form.